Mengoptimalkan Nilai Perusahaan: Dampak Profitabilitas dan Leverage, Dimoderasi oleh Ukuran Perusahaan - Ariwangsa, I G. N. Oka; Ernawati, Ni Luh; Laksmi P, Kadek Wulandari; Putra, Komang Satria Wibawa (Universitas Mataram, 2024)
The increase in the number of manufacturing companies expanding in Indonesia recently is very potential seen from Indonesia as a developing country. A company's value is reflected in its share price, with a higher share price indicating greater financial success for its shareholders, a company's value refers to the present value of a company, which is determined by the anticipation of future cash inflows it may generate (Abidin, 2022). Stock price fluctuations are a direct manifestation of the effectiveness of company management. Investors and potential investors are careful in making investment choices because they carefully evaluate various facts (Besim, 2023). Signaling theory, describes the method a company uses to proactively communicate to investors about a company's future plans and strategies. Company signals are one of the ways signal theory is realized (Fauziah 2018). The study focused on eleven pharmaceutical companies engaged in the subsector, listed on the Indonesia Stock Exchange (IDX), during the period 2018 to 2022. The hypothesis was assessed in this study using Smart Partial Least Square (PLS) Version 4.0. The findings show that profitability and leverage have a positive influence on a company's value. In addition, the correlation between these two variables further increases when considering the size of the company.